2015
DOI: 10.4103/0366-6999.149211
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Regional and Global Left Ventricular Myocardial Function Using Strain and Strain-rate Imaging in Patients with Metabolic Syndrome

Abstract: Background:Strain and strain-rate imaging (SRI) have been found clinically useful in the assessment of cardiac systolic and diastolic function as well as providing new insights in deciphering cardiac physiology and mechanics in cardiomyopathies, and identifying early subclinical changes in various pathologies. The aim of this study was to evaluate the regional and global left ventricular (LV) myocardial function in metabolic syndrome (MS) with SRI so that we can provide more myocardial small lesions in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
6
8
0
1
Order By: Relevance
“…Interestingly, the resting EF exhibited a weak correlation with exercise capacity, while GLS, another assessment of myocardial systolic function, showed a relationship with peakVO 2 ( r = .32, P < .001) (Figure ). Nevertheless, we consider that EF was accurately measured in 3D echocardiography; EF is a markedly load‐dependent parameter that cannot accurately assess the functional status of the heart . However, the GLS is a reproducible parameter of global systolic function that is less influenced by load and has been demonstrated to have superior prognostic properties to LVEF in major observational studies .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the resting EF exhibited a weak correlation with exercise capacity, while GLS, another assessment of myocardial systolic function, showed a relationship with peakVO 2 ( r = .32, P < .001) (Figure ). Nevertheless, we consider that EF was accurately measured in 3D echocardiography; EF is a markedly load‐dependent parameter that cannot accurately assess the functional status of the heart . However, the GLS is a reproducible parameter of global systolic function that is less influenced by load and has been demonstrated to have superior prognostic properties to LVEF in major observational studies .…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, we consider that EF was accurately measured in 3D echocardiography; EF is a markedly load-dependent parameter that cannot accurately assess the functional status of the heart. 26 However, the GLS is a reproducible parameter of global systolic function that is less influenced by load and has been demonstrated to have superior prognostic properties to LVEF in major observational studies. 27 Our results were consistent with the study 3D EF = three-dimensional ejection fraction; LA index = left atrium volume index; EDT = early diastolic peak velocity deceleration time; E/e = ratio of early diastolic peak velocity to the early diastolic peak velocity of the mitral annulus; E/V p = the ratio of early mitral diastolic peak velocity to the mitral flow propagation velocity; GLS = global longitudinal systolic peak strain; GCS = global circumferential systolic peak strain; GRS = global radial systolic peak strain; 25%(50%) Untwist = the amount of untwisting at 25% (50%) of the untwisting duration.…”
Section: Lvef and Additive Value Of Longitudinal LV Functionmentioning
confidence: 99%
“…These findings were compatible with the study of Qin Wang et al (12) who studied 39 metabolic syndrome subjects with normal ejection fraction and 39 control subjects of similar age and found that; significant differences were observed between MS and the control group in most of the parameters of Strain, SR (s -1 ), SRIVR (s -1 ) in LV function and shows that assessment of myocardial function using SRI could be more accurate in MS patient evaluation than conventional echocardiography alone.…”
Section: B-strain Ratesupporting
confidence: 94%
“…These findings were similar to Qin Wang and his colleagues (12) who studied early detection of regional and global left ventricular myocardial function, that shows no significant difference was observed among the groups regarding age, sex, heart rate. There were significant differences in W.…”
Section: B-strain Ratesupporting
confidence: 89%
See 1 more Smart Citation